Understanding Primary School Students’ Knowledge and Attitudes Towards Water Management: Insights from Environmental Education - Oana Irimia; Claudia Tomozei; Mirela Panainte-Lehadus; Dana Chitimus; Florin Nedeff; Narcis Barsan; Emilian Mosnegutu; Diana Mirila (Societies)
Environmental education is a vital strategy for conservation and protection, creating collaborative spaces for scientists, community members, and other stakeholders. Across various countries, educational curricula include courses aimed at teaching the younger generation about environmental protection. Interactive and practical educational programs, along with the involvement of parents and the community, enhance learning and create connections between school and daily life. Curriculum changes are influenced by several factors, including children’s understanding and application of these concepts. Various methods, such as questionnaire analysis, have been developed for this purpose. This study assessed the knowledge levels and behaviors regarding the environmental factor “water” among primary school students in Bacău, Romania. Conducted through a questionnaire method, the survey included 308 students from grades 2 to 4. The findings highlight the significance of environmental education in primary schools, preparing children to act responsibly towards the environment. It is recommended to implement interactive educational programs and foster partnerships with the community and local organizations to promote water conservation and reduce consumption, thereby cultivating a long-term sustainable culture.